Low-Frequency Ultrasound Debridement in Chronic Wound Healing: A Systematic Review of Current Evidence. Issue 1 (February 2017) - Chang, Ying-Ju Ruby; Perry, Julie; Cross, Karen
Chronic wounds are painful and debilitating to patients, pose a clinical challenge to physicians, and impose financial burden on the health-care system. New treatment options are therefore highly sought after. Ultrasound debridement is a promising technology that functions to disperse bacterial biofilms and stimulate wound healing. In this review, we focus on low-frequency ultrasound (20-60 kHz) and summarize the findings of 25 recent studies examining ultrasound efficacy. Ultrasound debridement appears to be most effective when used 3 times a week and has the potential to decrease exudate and slough, decrease patient pain, disperse biofilms, and increase healing in wounds of various etiology. Although current studies are generally of smaller size, the results are promising and we recommend the testing of low-frequency ultrasound therapy in clinical practice on a larger scale.